PENENTUAN NILAI TUKAR: PENGUJIAN PURCHASING POWER PARITY DI INDONESIA - Kusumastuti, Sri Yani (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2004)
This paper provides a test of purchasing power parity (PPP) as an explanation for longtermforeign exchange rate movement. We impose symmetry and proportionality restrictions ofPPP to data drawn from the period 1969.1 through 2001.4. The tests are also run for sub-periods. Symmetry and proportionality restrictions find little support for the unit root tests though the Johansen test suggests that foreign exchange rate and inflation rate are linked in a long run sense. Error correction models are then estimated on the basis of the assumption that the United States inflation rate is exogenous. The error correction models result also rejects the PPP.Keywords: purchasing power parity, exchage rate